Effect of pretreatment soaking duration to characteristic of ultrafine treated rice husk ash (UFTRHA) as supplementary cementing material (SCM) - Nuruddin, Muhd Fadhil; Saad, Siti Asmahani; Shafiq, Nasir; Ali, Maisarah (Asian Research Publishing Network, 2016)

(untitled)
Rice husk ash (RHA) possesses high content of amorphous silica that is essential in pozzolanic reaction of supplementary cementing material (SCM) in concrete strength enhancement. However, usage of conventional RHA is unfavourable in current concrete industry. One of the reason that hindered the utilization of conventional RHA nowadays is due to its properties inconsistency namely chemical and mineralogical properties. In this regard, improvement on the RHA properties by introduction of chemical pre-treatment prior to burning procedure is seen as an excellent way to reach the goal. In this research, raw rice husk was soaked in 0.1M hydrochloric acid (HCl) solution from one to three hours. After that, the pre-treated rice husk was ground using planetary ball mill for 15 minutes. The effect of pre-treatment soaking time to alkali metal removal and its chemical composition, mineralogical properties, particle size analysis as well as specific surface area of ultra fine treated rice husk ash (UFTRHA) were determined accordingly. As for alkali metal removal analysis, potassium element had the highest removal concentration with value of 55.35 mg/l. Meanwhile, amorphous silica content of the optimum sample was recorded as 96.00% at three hours of pretreatment soaking period. In terms of particle size and specific surface, it was also observed that, three hours of pretreatment soaking duration was sufficient to produce finest size of UFTRHA where d(0.1), d(0.5) and d(0.9) were obtained as 1.417μm, 4.493μm and 14.884μm respectively and the largest specific surface area of 196.61m2/g. Keywords: treated rice husk ash, supplementary cementing material, and alkali metal removal.